2021
DOI: 10.54536/ajaset.v5i2.96
|View full text |Cite
|
Sign up to set email alerts
|

Struggling Learners' Achievement Level Using Electronic Strategic Intervention Material In Mathematics (ESIMATH)

Abstract: This study focused on the achievement levels of Grade 11 struggling learners using an electronic Strategic Intervention Material in Mathematics (eSIMath) in teaching least mastered competencies in the subject, Statistics and Probability for Senior High School. A Solomon four-group quasi-experimental research design was employed to two classes using eSIMath-based instruction, and two classes via conventional instruction, who were identified through a local diagnostic examination given by the teacher-researcher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The result from the analysis points out that the Another study by Balazo (2021) provides evidence that eSIMath can be an effective intervention for struggling learners in mathematics. The study showed that the group that received eSIMath-based instruction performed significantly better on the posttest than the group that received conventional instruction.…”
Section: Scores Of Studentsmentioning
confidence: 94%
“…The result from the analysis points out that the Another study by Balazo (2021) provides evidence that eSIMath can be an effective intervention for struggling learners in mathematics. The study showed that the group that received eSIMath-based instruction performed significantly better on the posttest than the group that received conventional instruction.…”
Section: Scores Of Studentsmentioning
confidence: 94%